Regulating Photocatalytic Selectivity of Anatase TiO2 with 101, 001, and 111 Facets. Issue 12 (18th August 2014) - Zhang, Jun; Chen, Sheng; Qian, Lisha; Tao, Xi; Yang, Lingxia; Wang, Hongbo; Li, Yangyang; Zhang, Erpan; Xi, Junhua; Ji, Zhenguo
Abstract : In this work, we demonstrate a novel approach to control the photocatalytic selectivity of TiO2 though different dominant crystal facets. 101, 111, and 001 facets exposed nanoscale anatase TiO2 were obtained by a simple hydrothermal route with different ratio of NH4 + and F −, then a calcined progress to clear surface adsorbent atoms. Results reveal that 101 exposed TiO2 has some remain binding N with a mode of unsaturated N3c exhibits selectively photocatalytic degradation of methylene orange (MO) in a methylene blue (MB) and methyl orange (MO) mixed solution, whereas TiO2 with exposed 111 and 001 facets exhibits photocatalytic selectivity for MB. The 111 facets of anatase TiO2 exhibit a better photocatalytic selective ability than 001 facets. It confirms that the photocatalytic selectivity can be affected by different dominant crystal facets. In a deeper analysis, there are many unsaturated O2c on the surface of 001 and 111 facets, which enhances adsorbent selectivity and relevant photocatalytic activity of MB, at the same time, the unsaturated O2c on the surface of 111 facets is much more than that on the surface of 001 facets results in a better photocatalytic selectivity of 111 facets. This research hopes that developing a new strategy for photocatalytic selectivity and providing a deeper understanding of different crystal facets of TiO2 .